Loss of desiccation tolerance during imbibition-germination in maize seeds - Rangel-Fajardo María Alma; Córdova-Téllez Leobigildo; Cárdenas-Soriano Elizabeth (Revista Mexicana de Ciencias Agrícolas, 2018)
Orthodox seeds near maturity acquire desiccation tolerance, however during this imbibition-germination is lost. The time that occurs between species even between batches of the same species is variable. When the loss of desiccation tolerance in maize seeds during imbibition, germination occurs is determined, and also the behavior of lipid bodies relative to the loss of tolerance was observed. Maize seeds of line 231 were imbibed in water and with various concentrations of polyethylene glycol 8 000. The imbibition kinetics was quantified in periods of eight hours to 40 hours and the loss of tolerance to desiccation is estimated by testing standard germination, conductivity electrical and accelerated aging. Embryonic axes were processed and observed in the transmission electron microscope. The loss of desiccation tolerance was presented at 32 h of imbibition water contents of 300 g H2O kg1 and 520 g H2O kg1 seed and embryo respectively.At this time the conductivity increases from 7.26 to 15.63 g μSm-1g-1 while the germination viability decreased 27 and 84% respectively. The movement of lipid bodies during imbibition-germination occurs between 24 h and 32 h, causing changes to the membrane with dried, so the role of these, besides being a source of energy during germination, provide membrane protection during desiccation.